PHYSICOCHEMICAL EVALUATION AND TABLET FORMULATION PROPERTIES OF SHEA TREE GUM - Kipo, Samuel Lugrie; Oppong, Esther Eshun; Kwakye, Kwabena Ofori- (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: This study focused on evaluating the physicochemical and tablet formulation properties of shea tree (Vitellaria paradoxa) gum, using paracetamol as a model drug. Methods: Crude shea gum was purified and the physicochemical properties, namely: Moisture content, insoluble matter, solubility, swelling capacity, viscosity, hydration capacity, flow properties, and metallic ion content evaluated. The binding properties of shea gum (5-20% w/v) were investigated, using acacia gum as a standard binder. The physical properties, in vitro dissolution and dissolution efficiency (DE) of the tablets, were determined. The dissolution data were statistically evaluated using the T-test and the similarity factor (f2). Results: The physicochemical properties of the gum evaluated were found to be satisfactory and within official specifications. Atomic absorption spectrophotometric analysis of the gums showed that the crude gum had higher metallic ion content than the purified gum. The gum purification process caused a substantial reduction (17-74%) in the mineral ion content of shea gum. Granules prepared with shea gum exhibited good flow properties evidenced by their optimal Hausner ratio, angle of repose and Carr's index values. The granule flow properties, as well as the physical properties of shea gum tablets, were similar to that prepared with acacia gum. The DE of both shea gum and acacia gum tablets decreased with increase in binder concentration. Comparative studies on the tablets using DE, T-test and similarity factor (f2), showed that the binding effect of shea gum was comparable to that of acacia gum (p>0.05; f2 ≥50) at the same concentration. Conclusion: Shea tree gum has potential as a binder in pharmaceutical tablet formulations. Keywords: Vitellaria paradoxa, Viscosity, Wet granulation, Tablet binder, Dissolution efficiency, Similarity factor